Lung Ultrasound in Early Diagnosis of Neonatal Ventilator Associated Pneumonia before Any Radiographic or Laboratory Changes - Mohammed Ibrahim; Ahmed Omran; Mostafa Ibrahim; Nouran Bioumy; Sonya El-Sharkawy (Case Reports in Pediatrics)
Neonatal pneumonia is reported to be the primary cause of neonatal respiratory failure and one of the common causes of neonatal hospitalization and death in developing countries. Chest X-ray was considered the gold standard for diagnosis of neonatal pneumonia. Lung ultrasonography has been described as a valuable noninvasive tool for the diagnosis of many neonatal pulmonary diseases. We report a case of ventilation associated neonatal pneumonia with very early diagnosis using lung ultrasound before any significant radiographic changes in chest X-ray or laboratory findings suggestive of infection.